Arterial pulse waveform and pulse wave velocity - Sng, Gabriela Jing Hui (Nanyang Technological University, 2023)
This study aimed to investigate the potential of arterial pulse waveform (APW) analysis as a tool for predicting arterial age of subjects through the use of a pressure independent index (PII) based on the shape of APW. 3 different PIIs were studied and the results showed that PII_1= t_1/t_2 produced the highest R-Squared value. A linear regression model was used to predict the arterial health, with seven random data sets taken to test the trained model which was based on 53 data sets. Despite the relatively sufficient R-Squared value of PII, further research is needed to improve the accuracy and precision of data taken. With further improvements made to the PulseTraxerTM PT8080, other parameters could be uncovered and more PIIs may be discovered that predicts the arterial age better than PII1. Nonetheless, the study represents an important step forward in the field of cardiovascular health and provides a promising avenue for future research and clinical practice. By leveraging the power of APW analysis, we can improve our understanding of arterial aging and develop more effective strategies for promoting cardiovascular health and reducing the burden of CVDs.